Analyzing critical thinking enhancement and moment of inertia understanding through inquiry based virtual labs - Sony Yunior Erlangga; Sarwanto; Harlita; Isnanik Juni Fitriyah; Resti Yektyastuti; Krida Singgih Kuncoro; Betty Kusumaningrum (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study examines the effectiveness of inquiry-based virtual laboratory modules in improving civil engineering students' conceptual understanding of moment of inertia, with critical thinking skills as a moderating factor. Using a quasi-experimental 2x2 factorial design, 60 students were divided into experimental and control groups. The experimental group engaged with virtual lab modules featuring interactive simulations and case-based learning, while the control group received conventional lecture-based instruction. Results indicated significantly higher learning outcomes in the experimental group (mean score = 58.9) compared to the control group (46.5), with critical thinking skills further amplifying this effect. ANOVA analysis confirmed the significant impact of the intervention (F = 21.83, p < 0.001). The study highlights the importance of integrating technology with pedagogical strategies that foster critical analysis and self-directed exploration. These findings contribute to engineering education by demonstrating how virtual labs, when combined with inquiry-based learning, can bridge the gap between theoretical knowledge and practical application while accommodating diverse learning needs. Recommendations include curriculum integration of such modules and professional development for educators in implementing technology-enhanced, inquiry driven approaches.